Lessons Learned from Policy Changes in the Poverty Alleviation Program in Jeneponto Regency, South Sulawesi Province - Aslinda, Andi; Akmal, Muh Ikramullah; Zainal, Henni; Haerul, Haerul (Darul Yasin Al Sys, 2025)
This study analyzes the policy learning processes underlying poverty alleviation policy changes in Jeneponto Regency, South Sulawesi Province. With a poverty rate of 13.06%—representing approximately 49,700 individuals in 2023—Jeneponto requires a policy framework that moves beyond charitable interventions toward strategies grounded in empowerment and institutional learning. Employing a qualitative case study design, data were collected through in-depth interviews, observation, and document analysis, and were processed using the Miles and Huberman interactive model, encompassing data reduction, data display, and conclusion drawing. The findings indicate that poverty alleviation policy changes in Jeneponto are not limited to technical or administrative adjustments but emerge from an iterative policy learning process. This approach has contributed to a modest reduction in the poverty rate from 13.26% in 2022 to 13.06% in 2023. While the decrease is incremental, it signifies a shift toward more reflective, responsive, and adaptive policymaking tailored to community needs. The study concludes that policy learning—through institutional reflexivity and stakeholder engagement—is central to enhancing the effectiveness and sustainability of regional poverty alleviation efforts. The Jeneponto government’s evolving capacity for institutional and social adaptation underscores the importance of continuous learning in advancing public policy governance.